In Situ X-ray Absorption Spectroscopy to Monitor the Degradation of Fe/N/C Cathode Catalyst in Proton Exchange Membrane Fuel Cells. Issue 1 (29th January 2021) - Nabae, Y.; Yuan, Q.; Nagata, S.; Kusaba, K.; Aoki, T.; Takao, N.; Itoh, T.; Arao, M.; Imai, H.; Higashi, K.; Sakata, T.; Uruga, T.; et al.
Abstract : Understanding the degradation mechanism of Fe/N/C cathode catalysts in proton exchange membrane fuel cells (PEMFCs) is important. We studied the degradation of an Fe/N/C catalyst prepared from polyimide nanoparticles in an in situ cell by X-ray absorption spectroscopy (XAS). This technique enables real-time monitoring of the Fe species during a fuel cell operation. The Fe K-edge absorption spectra were recorded during the continuous operation of the fuel cell. Initially during the fuel cell operation, the Fe species were atomically isolated and their valence state was found to be 3+. The spectra gradually changed during the first few hours of operation, suggesting the dissolution of the Fe species from the active sites, whereas the fuel cell performance continued to decrease during the eight hours of operation. The demetallation from the FeN x centers during the first few hours has been successfully monitored in real time, while the remaining FeN x centers seem to be stable in the following fuel cell operating condition.